Depression development in patients with celiac disease - Agata Pikulicka; Katarzyna Pacek; Małgorzata Piekarska; Radosław Kasperski; Klaudia Jedlina; Izabela Szulc; Weronika Swacha (Kazimierz Wielki University, 2022)
Due to the increasing number of patients suffering from celiac disease (CD) and difficulties in diagnosing, scientists raise awareness of different symptoms that patients might present. CD is an autoimmune, genetical disease of small intestine however, symptoms might be related to many different systems apart from gastrointestinal one, for instance nervous system. A common and non-specific symptom of untreated CD might be depression. A gluten intake by patients with genetical predisposition results in antibodies production which can affect central nervous system causing depression. Moreover, we observe imbalance between amino acids and its metabolites, for example serotonin, which lead to mood disorder. In those patients who suffer from drug-resistant depression, testing for CD should be done and if they are positive, the patient should immediately start a gluten-free diet. This action could reduce symptoms of depression. The following article is a review of current knowledge related to correlation between CD and depression, its pathomechanism and gluten-free diet as a possible way of treatment. This article is based on available publications in Pubmed and Google Scholar databases.